Intention of behavior changing in adolescents to practice leisure physical activities - Maciel, Marcos Gonçalves; Veiga, Ricardo Teixeira (Brazilian journal of physical education and sport, 2012)
The aim of this study was to investigate the intention of behavior changing in adolescents from different socioeconomic status (SES) to leisure physical activities, adopting the transtheoretical model and the Theory of Planned Behavior (TPB). We conducted a cross-sectional study involving 416 adolescents belonging to high schools in the cities of Belo Horizonte and Contagem / MG, with a mean age of 16.4 ± 1.2 years. Analyses were performed using descriptive and parametric statistics (ANOVA and logistic regression). The results show that most of teenagers are inactive during leisure time, and the variables, sex, attitude and perceived control are the most relevant factors to rate the level of leisure physical activity, and social variables (socioeconomic status and standard subjective) are of less importance in predicting the intention to change behavior to practice these activities.